al 'Alaqah baina al Qalq wa Mahaarah al Kitaabah Laday Thullab al Madrasah al Tsanawiyah al Islamiyah al Hukumiyah 5 Bogor - Septiani, Wulan; Alawiyah, N Lalah; Ridlo, Ubaid (IAIN Bone, 2025)
This research aims to identify the level of writing anxiety among tenth-grade students at MAN 5 Bogor and its relationship with their writing skills. The study employs a quantitative correlational method, with a sample of 74 students selected through Proportional Random Sampling from a total population of 285 students. Data collection techniques included a writing anxiety questionnaire based on the Second Language Writing Anxiety Inventory (SLWAI) by Cheng, using a Likert scale, as well as interviews and writing tests. The collected data was analyzed using the Product Moment Correlation formula. The results indicate that students’ writing anxiety falls into the